A study of level of motivation and financial literacy among undergraduates in Singapore. - Koh, Kai Xiang. (2009)
This paper aims to study the motivational factors that influence Singapore undergraduates’ motivation to gain financial literacy, and in turn investigate how motivation affects their level of financial literacy. The primary data for this research was collected by the means of a survey which was conducted on 220 undergraduates from three local universities.